Non-Similar Comutational Solutions for Double-Diffusive MHD Transport Phenomena for Non-Newtnian Nanofluid From a Horizontal Circular Cylinder - Ramachandra Prasad V.; Abdul gaffar S.; Rushi Kumar B. (Nonlinear Engineering, 2019)
This article aims to study theoretically the combined magneto hydrodynamic flows of casson viscoplastic nanofluid from a horizontal isothermal circular cylinder in non-Darcy porous medium. The impacts of Brownian motion and thermophoresis are consolidated and studied. The governing partial differential equations are converted into nonlinear ordinary differential equations using suitable non-similarity transformation and are solved numerically using Keller-Box finite difference technique. The numerical method is validated with previous published work and the results are found to be in excellent agreement. Numerical results for velocity, temperature, concentration along with skin friction coefficient, heat and mass transfer rate are discussed for various values of physical parameters. It is observed that velocity, heat and mass transfer rate are increased with increasing casson fluid parameter whereas temperature, concentration and skin friction are decreased. Velocity is reduced with increasing Forchheimer parameter whereas temperature and nano-particle concentration are both enhanced. An increase in magnetic parameter is seen to increase temperature and concentration whereas velocity, skin friction heat and mass transfer rate are decreased. The present model finds applications in electric-conductive nano-materials of potential use in aviation and different enterprises, energy systems and thermal enhancement of industrial flow processes.